Internet Memes as Alternative Frames in Global Media Coverage of the Gaza Conflict - Margaret Solo-Anaeto; Funmi Falobi; Abdullahi Aliyu Maiwada; Joseph Ifeoluwa Joy (Budapest International Research and Critics University, 2026)
The rapid evolution of digital communication technologies has significantly transformed the ways in which global audiences access and interpret international news, with social media platforms emerging as dominant channels of information dissemination. Within this digital ecosystem, internet memes have evolved from mere entertainment artifacts into powerful tools of communication that shape political discourse and public opinion. This paper examines the role of internet memes as instruments of international coverage of the Gaza War, exploring their capacity to simplify complex conflict narratives, influence audience perceptions, and contribute to the framing of global events. Within the context of the existing literature, the paper conceptualises memes as participatory media forms that combine visual and textual elements, enabling rapid circulation, emotional engagement, and ideological expression across diverse audiences. Using Framing Theory, the paper analyses how memes selectively present aspects of the Gaza conflict, emphasizing particular viewpoints, emotions, and interpretations while potentially marginalising others. The paper argues that memes function as alternative communicative frames that can both legitimize and delegitimize political actors, amplify humanitarian concerns, and foster global solidarity. At the same time, their brevity, humor, and symbolic nature pose risks of oversimplification, misinformation, and ideological distortion, particularly within the fast-paced and algorithm-driven environment of social media. The paper concludes that internet memes occupy a dual position as both facilitators of engagement and potential sources of distortion in international conflict reporting. As digital culture continues to evolve, memes will remain central to how global audiences consume, interpret, and respond to international events.